RENMINBI INTERNATIONALIZATION, AN INTERPRETATION OF REAL CHINA ORIENTATIONS AND POSSIBLE EFFECTS FOR HONG KONG STOCK EXCHANGE MARKET - Valacchi, Francesco (European Scientific Journal, ESJ, 2015)
The article is a research on Chinese Political Economy, dealing about Renminbi Internationalization and its effects on Hong Kong Stock Exchange. In the article I went through the step conducted by Chinese government to internationalize its currency. Then tried to analyze real Chinese intentions and actions, examining indexes of Hong Kong market to understand what are the effects on Hong Kong finance market. Hong Kong is an ideal stage to measure perceptions of benefits underpinned to Renminbi (RMB) internationalization. In fact Hong Kong is part of People’s Republic of China as a Special Administrative Region and benefits from this situation, having particular political and economic autonomies. In particular Hong Kong has its own currency and political economy and can deal with Chinese economy from the particular position of an external insider. Hong Kong is also the first market where have been issued bonds in Renminbi and is probably going to become the most affected economy from the internationalization. I conducted an analysis of possible real benefits (or negative effects) that Hong Kong and its population could have from an internationalized RMB taking in account effects of Chinese step toward Internationalization on Hong Kong finance market. In conducting my research I found out four steps particularly representatives of RMB internationalization, for each step I analyzed Hong Kong financial market behavior and I tried to assess the effects of a definitive RMB Internationalization. I finally tried to conclude if process has to be considered and advantage or disadvantage for Hong Kong and what could be better actions for Special Administrative Region to take in order to avoid or diminish possible negative effects of RMB Internationalization process.